Digital Marketing Kuliner Online Oleh Reseller Prespektif Fikih Muamalah - Mutia Izzatun Nurul Imamah (CV. Creative Tugu Pena, 2024)
This study examines the implementation of online culinary digital marketing by resellers from the perspective of fiqh muamalah, with a focus on the study in Gedangan Hamlet, Gedangan Village, Mojowarno District, Jombang Regency. Using a qualitative approach, this study aims to analyze the suitability of digital marketing practices with sharia principles in the context of online culinary trade. Direct observation, documentation studies, and in-depth interviews with six online culinary business actors were used to gather data. According to the study's findings, online culinary digital marketing by resellers has not quite complied with the requirements of fiqh muamalah, particularly with regard to contracts and transaction transparency. The majority of business actors use WhatsApp, Facebook, and Instagram platforms with a profit-sharing system of between 10-20%, but without adequate formal documentation. This research shows that the majority of business actors carry out promotions using other parties' product content without permission and take advantage without any formal agreement. From the perspective of muamalah fiqh, this practice does not meet the legal requirements for buying and selling because the goods sold are not their own or do not have official power of attorney from the owner. To overcome this problem, the study recommends the standardization of reseller contracts in accordance with the principles of muamalah fiqh, including clear documentation of agreements. In addition, it is important to form a sharia business community to support the implementation of sharia-compliant digital marketing.